STUDENT SATISFACTION AND THE QUALITY OF ACADEMIC GUIDANCE SERVICES AT PRINCE SATTAM BIN ABDULAZIZ UNIVERSITY: EMPIRICAL EVIDENCE - GalalAbdulqader Ahmed Alashaari, Abdul-Wasea Abdul-Ghani Almekhlafi (International Journal of Advanced Science and Technology, 2020)
This research aims to measure the level students' satisfaction at Prince Sattam bin Abdulaziz University on the quality of academic guidance services provided to them, and to know the differences in the students' satisfaction with those services according to the variables of the genderand the region (university branch). The questionnaire was used as a sample measurement tool consisting of 2237 students from theuniversity various colleges and programs, in its various branches. The questionnaire consisted of 22 paragraphs distributed over 4 axes, namely: academic guidance, professional, psychological, personal advice andelectronic advice.The results showed that there is an average degree of satisfaction with the quality of guidance services provided to students, and there are significant differences at the level of significance of 5% between the averages of students' satisfaction due to the gender variable and the region variable (university branch). Among the most important recommendations that the two researchers provided in the light of the results is the increase of the university’s interest in students' needs, meeting their expectations and taking students’ satisfaction into account as a component of quality and academic accreditation.